2010
DOI: 10.1063/1.3276741
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of wakefields on three-dimensional particle arrangements

Abstract: The role of wakefields on the three-dimensional (3D) particle arrangement in finite dust clouds at low neutral gas pressures is investigated experimentally. Using a novel stereoscopic digital in-line holography approach for the instantaneous measurement of the 3D particle positions, the structural properties of finite dust clouds are studied. The competition of a nested shell structure (known from Yukawa balls) and vertical particle chains (known for particle clouds confined in the plasma sheath) results in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 35 publications
1
61
0
Order By: Relevance
“…In the plasma sheath region, where strong electric fields are present, the grains form vertically aligned 'dust molecules' and, with the help of a confining potential, long particle strings can be created, e.g. [5,6,7]. The vertical alignment of particles is not explainable with a purely repulsive grain interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In the plasma sheath region, where strong electric fields are present, the grains form vertically aligned 'dust molecules' and, with the help of a confining potential, long particle strings can be created, e.g. [5,6,7]. The vertical alignment of particles is not explainable with a purely repulsive grain interaction.…”
Section: Introductionmentioning
confidence: 99%
“…in a Yukawa system. In dusty plasma experiments the friction coefficient can be within a wide range [10,14,37], depending on the gas pressure. We thus expect that it should be possible to observe the modes in experiments.…”
Section: Influence Of Dampingmentioning
confidence: 99%
“…The (linear response) theory of Lampe et al [19] for like particles in confining wells indicates that anharmonic (steep wall) well structure is required but can then explain oblique alignment. Recently Kroll et al [20] have observed return transitions to vertical alignment from metastable oblique alignment states that again have angles no less than 45 o for like particles. Hebner and Riley (2003-4) [21,22], in contrast, observed the dynamics of two interacting particles at low neutral pressure, moving in one horizontal dimension at almost fixed (but different) heights determined by the various different sizes of the particles.…”
Section: Introductionmentioning
confidence: 99%